The divine courtroom in comparative perspective - Mermelstein, Ari.; Holtz, Shalom E. (Biblical Interpretation Series, 2015)
Contributors to The Divine Courtroom in Comparative Perspective treat one of the most pervasive religious metaphors, that of the divine courtroom, in both its historical and thematic senses. In order to shed light on the various manifestations of the divine courtroom, this volume consists of essays by scholars of the ancient Near East, Hebrew Bible, Second Temple Judaism, early Christianity, Talmud, Islam, medieval Judaism, and classical Greek literature. Contributions to the volume primarily center upon three related facets of the divine courtroom: the role of the divine courtroom in the earthly legal system; the divine courtroom as the site of historical justice; and the divine courtroom as the venue in which God is called to answer for his own unjust acts.